ANALISA SISTEM PENDUKUNG KEPUTUSAN UNTUK PROSES KENAIKAN JABATAN PADA PT. X - Endang Lestari Ruskan (Universitas Sriwijaya, 2009)
Decision Support System is a case tool used to ease a decision makers to be more quickly and objectively. A case study of PT. X is one of the objects which will make the selection of employees to promote. The problem is determining what criteria will be used as determinant factors and how to make a prototype? The research methodology used is the system analysis, design system and system implementation. Determination of criteria that will be chosen is a decision that must be taken by the head of the company Analytic Hierarchy Process (AHP) is a method or tool in decision making multi criteria by using the help of Expert Choice software. Results are used to facilitate the user in selecting employees who will be chosen to ascend to a certain position This prototype is expected to assist in accelerating the decision making of employees who elected to board positions. Keywords : Sistem pendukung keputusan, kenaikan Jabatan (promosi), karyawan, Metode AHP, Expert Choice